2020
DOI: 10.1038/s41598-020-65631-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar and crop straws on the bioavailability of cadmium in contaminated soil

Abstract: Numerous studies have been investigated the potential of biochar (BC) derived from various materials and crop straw (CS) to decrease the bioavailability of heavy metals in soil contaminated with cadmium (Cd), and thereby reduce their potential risk to human health and the ecological environment. However, little attention has been given to the comparison of heavy metal remediation efficiency using BC and CS such as peanut vine (PV) and rice straw (RS), especially in soil contaminated with Cd. Here, we explore i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Many soil modifiers, such as lime, iron-based materials, biochar, hydroxyapatite, zeolite, and crop straws, were added during the remediation of soil polluted with heavy metals [ 12 ]. Biochar represents a low-cost, environmentally friendly soil modifier widely used in the remediation of soil polluted with different heavy metals [ 13 , 14 ]. Previous studies indicated that Cd in soil can be fixed by using biochar [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many soil modifiers, such as lime, iron-based materials, biochar, hydroxyapatite, zeolite, and crop straws, were added during the remediation of soil polluted with heavy metals [ 12 ]. Biochar represents a low-cost, environmentally friendly soil modifier widely used in the remediation of soil polluted with different heavy metals [ 13 , 14 ]. Previous studies indicated that Cd in soil can be fixed by using biochar [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of biochar to heavy metal contaminated soil significantly enhanced the heavy metal remediation that was affected by sunflowers. Chen et al [29] studied whether Cd bioavailability was affected in soils containing biochar and crop straw. The results show that biochar amendments enhanced the peanut biomass and physiological quality, and biochar had a greater impact on immobilizing Cd in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…However, advantages and disadvantages between the economic cost (production) and benefit value (application) of biochar need to be carefully measured. In addition, to enhance economic availability, easier production processes and cheaper sources of raw biomass materials need to be discovered to enhance economic availability [116]. Heavy metals can contaminate faecal sludge if toilets are also used to dispose of materials other than faecal sludge [52].…”
Section: Challenges Sustainability and Potential In Application Of Biochar In Sludge Managementmentioning
confidence: 99%